Inwestycje w majątek trwały a wyniki ekonomiczno-finansowe spółdzielni mleczarskich - Pietrzak, Michał (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2014)
Even in the knowledge-based economy era tangible assets still matters. It is because the value of intangible assets steams from the combined bundle of both tangible and intangible resources. Therefore it is important issue to assess how investments in fixed assets are connected with business performance. This problem seems to be particularly interesting in the case of Polish dairy industry. It is important part of European and Polish agribusiness system. During transition in Poland a lot of investments in dairy industry were already done. There is substantial overcapacity noticed in this sector. However empirical evidence done on 18 Polish dairy cooperatives shows the positive correlation between modernity of fixed assets and intensity of developing them and economic performance of dairies.